Quality parameters of different oils and fried foods after repeated deep-fat frying - Polak, Tomaž (Array, 2020)
The aim of present study was to investigate the quality, stability and suitability of different frying oils (coconut, palm, frying mix, rapeseed and sunflower oil), the quality and stability of breaded and fried foods (chicken nuggets) and the applicability and suitability of certain parameters (fat absorption, acid number, peroxide number and thiobarbituric acid (TBA) number, fatty acid composition and acrylamide content) as well as sensory attributes to control the repeated deep-(fat) frying process. Three repeated deep-frying processes affected the hydrolytic and oxidation stability (increase in the peroxide number and TBA number), the sensory properties (darkening of the oil colour, occurrence of odd smell and aroma as well as rancidity in oils) and the fatty acid composition of oil and fried chicken nuggets, and the acrylamide content in the nuggets (from the second deep-frying process onwards). All oils used in study were suitable for deep-frying; in terms of stability, coconut oil (followed by sunflower, palm, frying mix and rapeseed oil) was most suitable; in terms of fatty acid composition, the frying mix, rapeseed and sunflower oil were most suitable; and in terms of acrylamide formation and sensory quality, coconut and palm oil were most suitable.